2020
DOI: 10.1186/s40068-020-00175-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adoption of improved structural soil and water conservation measures in Eastern Ethiopia

Abstract: Background: Agriculture remains to be the leading sector that contributes enormously to economic development in Ethiopia. Despite its significant contribution to livelihoods, the sector faces persistent challenges due to depletion of natural resources and soil erosion that resulted in diminishing crop and livestock productivity. In order to curb the effects of land degradation, the Government of Ethiopia has been taking serious measures to expand Soil and Water Conservation (SWC) practices throughout the count… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…Farmers want to invest more on the nearest farmlands as far away farmlands discouraged them to construct and maintain soil and water conservation practices. This result is in line with the previous studies [12,16,17,26] who reported that the longer the walking distance between farmland and residential area, the less in the adoption of soil and water conservation practices.…”
Section: Determinants For the Adoption Of Swc Measures In The Study Areasupporting
confidence: 93%
See 1 more Smart Citation
“…Farmers want to invest more on the nearest farmlands as far away farmlands discouraged them to construct and maintain soil and water conservation practices. This result is in line with the previous studies [12,16,17,26] who reported that the longer the walking distance between farmland and residential area, the less in the adoption of soil and water conservation practices.…”
Section: Determinants For the Adoption Of Swc Measures In The Study Areasupporting
confidence: 93%
“…The farmers' education status affects their use of soil and water conservation practices positively and significantly among the farmers of Lege-lafto watershed. This finding corroborates with the finding of previous studies [1,10,16,26] who stated that better education level of household heads having a strong and positive relationship with farmers' adoption of SWC conservation practices.…”
Section: Determinants For the Adoption Of Swc Measures In The Study Areasupporting
confidence: 92%
“…They indicated that the practice involves a lot of digging which is very challenging and requires more people to start using it. The issues discussed above support the indication of some studies conducted in the highlands of Ethiopia (e.g., Mekuriaw et al, 2018;Wordofa et al, 2020) that suggested that the active involvement of farmers and technical support from the government is crucial to start and sustain the implementation of physical SWC measures The difficulty in implementing exclosures and its sustainability concern relates to the collective action requirement of exclosure practices versus the reluctance of individuals in committing themselves to collective activities. During FGDs, farmers indicated that achieving consensus among community members is difficult, as farmers have diverse interests on communal lands and the ways they would like to use them for grazing animals.…”
Section: Factors Influencing Farmers' Decision and Their Implementati...mentioning
confidence: 82%
“…Although ordered probit and logit models yield similar inferences, they assume standard normal and logistic distributions of the error terms, respectively. An ordered probit model was used in this research as it is a commonly used tool in other related research such as [37][38][39][40][41][42].…”
Section: Specification Of the Econometric Modelmentioning
confidence: 99%